PROCEDURE FOR THE DIAGNOSIS OF TEMPOROMANDIBULAR JOINT DYSFUNCTIONS - Andrei Fachira; Carolina Susanu; Șerban Paul Popa; Oana Lorena Nistor; Mădălina Nicoleta Matei; Ovidiu Schipor; Gabi Topor; Corina Cecilia Manole Palivan; Sergiu Focșăneanu; Oleg Solomon (Romanian Society of Oral Rehabilitation, 2021)
The clinical examination of the temporomandibular dysfunctions regards the identification of occlusal disharmonies, the nature of muscular hyperactivity, the presence of signs/symptoms of temporomandibular joint dysfunctions. The specificity and sensitivity of paraclinical methods, based on relevant comparative studies, represent indices that are to be used in the process of choosing and applying investigation methods. There was accomplished a retrospective analysis (a case study) of 8 patients with condyle-disk assembly dysfunctions. The symptomatic triad (arthralgia, limitation/deviation of mandibular movements, joint noises) have served preventively for the identification of the clinical form of joint dysfunction. The complex data gathered from the clinical exam allowed us to differentiate and to identify the clinical form, based on several diagnostic criteria. The graphic recording of joint vibrations (Bio-JVA,Bio-Research,USA) and the parameter analysis (vibration peak, etc.) served for confirming the initial diagnosis. In the process of diagnosing the condyle-disk dysfunctions, the values of the parameters recorded by using the paraclinical method Bio-JointVibrationAnalysis,(Bio-JVA,Bio-Research,USA), serveas a proof for confirming the initial diagnosis.